2014
DOI: 10.1666/13-138
|View full text |Cite
|
Sign up to set email alerts
|

Epizoozoan Trepostome Bryozoans on Nautiloids from the Upper Ordovician (Katian) of the Cincinnati Arch Region, U.S.A.: An Assessment of Growth, form, and Water Flow Dynamics

Abstract: Spatiopora Ulrich, 1882 is a trepostome bryozoan that is found encrusting living orthoconic nautiloids in the Upper Ordovician (Katian) of North America, as do several other bryozoans. These epizoozoan bryozoans are characterized by possessing thin unilaminate zoaria with rows of elongate maculae, which may be monticulate and aligned coaxially to the host growth axis. These develop a distinctive linear shape in response to growing on a conical host, rather than as a response to channelized water flow along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Nautiloid cephalopods, part of the Palaeozoic Evolutionary Fauna (Sepkoski , , ), were a common basibiont for stenolaemate bryozoans (Wyse Jackson & Key ; Wyse Jackson et al . ). The timing of the diversification of bryozoans through the Ordovician (Taylor & Ernst ; Ernst ) roughly coincides with the diversification of trilobites (Adrain et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nautiloid cephalopods, part of the Palaeozoic Evolutionary Fauna (Sepkoski , , ), were a common basibiont for stenolaemate bryozoans (Wyse Jackson & Key ; Wyse Jackson et al . ). The timing of the diversification of bryozoans through the Ordovician (Taylor & Ernst ; Ernst ) roughly coincides with the diversification of trilobites (Adrain et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Taylor ) and cephalopods (Wyse Jackson & Key ; Wyse Jackson et al . ) all serve as basibionts for epibiont bryozoans and are well preserved in the fossil record.…”
Section: Methodsmentioning
confidence: 99%
“…Hederelloids have been reported to encrust externally shelled cephalopods before ( Thayer, 1974 ; Brassel, 1977 ; Bartels, Briggs & Brassel, 1998 ; Frey et al, 2014 ), but these are, to our knowledge, the first reported to encrust an ammonoid in vivo . Sclerobionts can provide also important information on paleoecology, sedimentary environments and taphonomy, both when they encrust shells in vivo or after death of their host ( Baird, Brett & Frey, 1989 ; Kacha & Šaric, 2009 ; Rakociński, 2011 ; Brett et al, 2012 ; Wilson & Taylor, 2013 ; Luci & Cichowolski, 2014 ; Wyse Jackson, Key & Coakley, 2014 ; Luci, Cichowolski & Aguirre-Urreta, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first example of bryoimmuration in the Cincinnatian is the encrustation of orthoconic nautiloid conchs by the trepostome Spatiopora and other bryozoans (Wyse Jackson et al 2014). These bryozoans encrusted the nautiloids while they were alive, almost completely covering the exterior surfaces with thin calcitic colonies containing maculae elongated parallel to the direction of water flow (Fig.…”
Section: Cincinnatian Bryoimmurationsmentioning
confidence: 99%